Virtual manipulatives in inquiry-based approach of 3D problems by French 5th graders - Pacurar, Ecaterina; Magot, Claude-Alexandre; Cabassut, Richard; Solon, Yohan (Teaching Mathematics and Computer Science, 2020)
The aim of this research is to study the appropriation of a 3D environment by learners in an a-didactical situation of problem solving. We try to evaluate the relevance of the virtual 3D environment in the development of students' cognitive and metacognitive abilities. We implanted a problem-solving activity related to a 3D cube situation with an empty part in the cube in different French primary school areas in May 2019. In the experimental group each learner works individually with a PC-computer where the virtual environment ANIPPO is implemented. In the control group the pupils work in a traditional class environment. We present the results of this pre-experimentation.Subject Classification: 97D50, 97U60, 97U70